2017
DOI: 10.3171/2017.5.focus17200
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive guidewireless, navigated pedicle screw placement: a technical report and case series

Abstract: OBJECTIVEPercutaneous pedicle screw insertion (PPSI) is a mainstay of minimally invasive spinal surgery. Traditionally, PPSI is a fluoroscopy-guided, multistep process involving traversing the pedicle with a Jamshidi needle, placement of a Kirschner wire (K-wire), placement of a soft-tissue dilator, pedicle tract tapping, and screw insertion over the K-wire. This study evaluates the accuracy and safety of PPSI with a simplified 2-step process using a navigated awl-tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In such cases, a percutaneous pedicle screw (PPS) is often employed. PPS placement is gradually being adopted for lumbar and thoracic spine surgery and is performed as a minimally invasive spinal fusion (MIST) approach [ 3 , 4 ]. A previous study showed that single-position surgery (SPS) could reduce the mean surgical time by approximately 34 minutes compared with dual-position surgery (DPS) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, a percutaneous pedicle screw (PPS) is often employed. PPS placement is gradually being adopted for lumbar and thoracic spine surgery and is performed as a minimally invasive spinal fusion (MIST) approach [ 3 , 4 ]. A previous study showed that single-position surgery (SPS) could reduce the mean surgical time by approximately 34 minutes compared with dual-position surgery (DPS) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new approaches and techniques are easier thanks to its application. 25 The objective of our study was to present our case series of HGS treated with transdiscal pedicle screws guided with 3D neuronavigation in adult patients with correct spinal balance and study whether image guidance can improve results compared with previous reports.…”
mentioning
confidence: 99%
“…In the traditional method, the accurate percutaneous pedicle screw placement relies heavily on fluoroscopy in order to obtain a proper screw trajectory. The insertion of guide-wire into the vertebral pedicle required numerous radiographic images in a trial-and-error fashion [23]. In recent years, a lot of systems or equipment [11,24,25] were introduced to facilitate the placement of percutaneous pedicle screw.…”
Section: Resultsmentioning
confidence: 99%